State Estimation for Neural Networks with Leakage Delay and Time-Varying Delays - Jing Liang; Zengshun Chen; Qiankun Song (Abstract and Applied Analysis)
The state estimation problem is investigated for neural networks with leakage delay and time-varying delay as well as for general activation functions. By constructing appropriate Lyapunov-Krasovskii functionals and employing matrix inequality techniques, a delay-dependent linear matrix inequalities (LMIs) condition is developed to estimate the neuron state with some observed output measurements such that the error-state system is globally asymptotically stable. An example is given to show the effectiveness of the proposed criterion.